Math

posted by .

Evaluate the limits lim x^3 + 3/ x->¤ 2x^3 + 4x + 1 lim 1 - cosx / x->o x^2

  • Math -

    Use l'Hôpitals rule:
    1.
    Lim (x->∞) (x³+3)/(2x³+4x+1)
    = Lim (x->∞) (3x²)/(6x²)
    = Lim (x->∞) (6x)/(12x)
    = Lim (x->∞) 1/2
    = 1/2

    Similarly for (1-cos(x))/(x²)
    = Lim (x->∞)

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Calculus..more help!

    I have a question relating to limits that I solved lim(x-->0) (1-cosx)/2x^2 I multiplied the numerator and denominator by (1+cosx) to get lim(x->0) (1-cos^2x)/2x^2(1+cosx) = lim(x->0)sin^2x/2x^2(1+cosx) the lim(x->0) (sinx/x)^2 …
  2. math

    i need some serious help with limits in pre-calc. here are a few questions that i really do not understand. 1. Evaluate: lim (3x^3-2x^2+5) x--> -1 2. Evaluate: lim [ln(4x+1) x-->2 3. Evaluate: lim[cos(pi x/3)] x-->2 4. Evaluate: …
  3. Calc. Limits

    Are these correct? lim x->0 (x)/(sqrt(x^2+4) - 2) I get 4/0= +/- infinity so lim x->0+ = + infinity?
  4. Maths Calculus Derivatives & Limits

    Using the definition of the derivative evaluate the following limits 1) Lim h---> 0 [ ( 8 + h )^1/3 - 2 ] / h 2) Lim x ---> pi/3 ( 2cosx - 1 ) / ( 3x - pi)
  5. Calculus

    Find the following limits algebraically or explain why they don’t exist. lim x->0 sin5x/2x lim x->0 1-cosx/x lim x->7 |x-7|/x-7 lim x->7 (/x+2)-3/x-7 lim h->0 (2+h)^3-8/h lim t->0 1/t - 1/t^2+t
  6. math

    Evaluate the following limits: (I) Lim. (x+1)/[1-sqrt(4+3x)] X >-1 (II) Lim. (2-3x-5x^2)/(1+2x^2) X >Infinite
  7. math

    Evaluate the following limits: (I) Lim. (x+1)/[1-sqrt(4+3x)] X >-1 (II) Lim. (2-3x-5x^2)/(1+2x^2) X >Infinite
  8. math

    Evaluate the following limits: (I) Lim. (x+1)/[1-sqrt(4+3x)] X >-1 (II) Lim. (2-3x-5x^2)/(1+2x^2) X >Infinite
  9. math

    Evaluate the following limits: (I) Lim. (x+1)/[1-sqrt(4+3x)] X >-1 (II) Lim. (2-3x-5x^2)/(1+2x^2) X >Infinite
  10. Math Limits

    Let, f(x) = {4, x<5, -3x, x=5, 10+x, x>5} Evaluate each of the following: a) lim(x-->5-)f(x)= b) lim(x--)5+)f(x)= c) f(5)=

More Similar Questions